The Practicality of Teaching Material Biology of Islamic-Science based on Augmented Reality - Meyninda Destiara (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
The results of the observation of biology learning in MAN 1 Banjarmasin are not familiar with using the teaching materials based on interactive technology. The development of teaching materials based on Augmented Reality Media can be a solution to solve these problems. This study aims to determine the practicality of biology teaching materials based on Islamic-science using Augmented Reality media. The design of this study uses the Borg and Gall models that have been approved to perfection of limited trial evaluation. The results showed that the teaching material developed was very practical to be used in supporting biology lessons in the Arthropods sub material.AbstrakHasil observasi pembelajaran biologi di MAN 1 Banjarmasin belum familiar menggunakan bahan ajar berbasis teknologi interaktif. Pengembangan bahan ajar berbasis media Augmented Reality dapat menjadi salah satu solusi untuk menyelesaikan permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui kepraktisan bahan ajar biologi berbasis islam-sains menggunakan media Augmented Reality. Desain penelitian ini menggunakan model Borg and Gall yang telah dimodifikasi yaitu sampai pada tahap penyempurnaan evaluasi dari uji coba terbatas. Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan sangat praktis digunakan dalam menunjang mata pelajaran biologi pada sub materi Arthropoda.